Advanced oxidation removal of hypophosphite by O3/H2O2 combined with sequential Fe(II) catalytic process. (August 2017) - Zhao, Zilong; Dong, Wenyi; Wang, Hongjie; Chen, Guanhan; Wang, Wei; Liu, Zekun; Gao, Yaguang; Zhou, Beili
Abstract: Elimination of hypophosphite (HP) was studied as an example of nickel plating effluents treatment by O3 /H2 O2 and sequential Fe(II) catalytic oxidation process. Performance assessment performed with artificial HP solution by varying initial pH and employing various oxidation processes clearly showed that the O3 /H2 O2 ─Fe(II) two-step oxidation process possessed the highest removal efficiency when operating under the same conditions. The effects of O3 dosing, H2 O2 concentration, Fe(II) addition and Fe(II) feeding time on the removal efficiency of HP were further evaluated in terms of apparent kinetic rate constant. Under improved conditions (initial HP concentration of 50 mg L −1, 75 mg L −1 O3, 1 mL L −1 H2 O2, 150 mg L −1 Fe(II) and pH 7.0), standard discharge (<0.5 mg L −1 in China) could be achieved, and the Fe(II) feeding time was found to be the limiting factor for the evolution of apparent kinetic rate constant in the second stage. Characterization studies showed that neutralization process after oxidation treatment favored the improvement of phosphorus removal due to the formation of more metal hydroxides. Moreover, as a comparison with lab-scale Fenton approach, the O3 /H2 O2 ─Fe(II) oxidation process had more competitive advantages with respect to applicable pH range, removal efficiency, sludge production as well as economic costs. Highlights: A novel protocol based on O3 /H2 O2 and sequential Fe(II) catalysis was presented. Hypophosphite and TP were effectively removed by two-step oxidation process. Fe(II) feeding time played an significant role for the hypophosphite oxidation. Real nickel plating effluents containing hypophosphite as case study. Fenton and two-step oxidation process for hypophosphite removal were compared.